2020
DOI: 10.1155/2020/9810170
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Differences in Expert Second-Opinion Consultation Cases at a Tertiary Sarcoma Center

Abstract: Soft tissue tumors are diagnostically challenging, and it is recommended that these are reported or reviewed by specialist soft tissue pathologists. We present our experience with second-opinion (consultation) cases in a specialist tertiary sarcoma center. The aim of this study was to determine areas of diagnostic difficulty in soft tissue pathology. We assessed 581 second-opinion cases which were reviewed by two experienced pathologists in a period of one year. There was 62% concordance between the original a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In consideration of both the rarity and intrinsic diagnostic complexity, published data indicate a rate of diagnostic inaccuracy that varies between 15 and 30% of cases. [1][2][3] Availability of structured pathology reporting may play an important role in improving the quality of the diagnostic process by ensuring better multidisciplinary communication. Moreover, more accurate data extraction by cancer registries allows more precise epidemiologic analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consideration of both the rarity and intrinsic diagnostic complexity, published data indicate a rate of diagnostic inaccuracy that varies between 15 and 30% of cases. [1][2][3] Availability of structured pathology reporting may play an important role in improving the quality of the diagnostic process by ensuring better multidisciplinary communication. Moreover, more accurate data extraction by cancer registries allows more precise epidemiologic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Soft-tissue sarcomas represent a heterogeneous group of malignancies, the diagnosis of which represents a global challenge. [1][2][3] Pathology reporting on sarcoma biopsy and resection specimens provides information that is essential to the management of patients, is used for clinical trials and tissue-based research, and is recorded in cancer registries. The relevance of accurate reporting is also underlined within current clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…10 Multiple studies of sarcomas have demonstrated a significant percent of cases demonstrating discordance between initial pathologic diagnoses and the diagnosis upon second opinion. [11][12][13][14] In the present case, the diagnosis of Ewing sarcoma still relies heavily on EWSR1 translocation detection by FISH, 15 which in the case of cutaneous Ewing sarcoma, can be problematic as it: (1) does not identify the EWSR1 binding partner and (2) can be negative when non-FLI1 Ewing fusion types are present, such as EWSR1-ERG. 16 Cutaneous Ewing sarcomas harboring an EWSR1-ERG fusion are reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In low patient volume healthcare settings, diagnosis may be provided by pathologists without advanced training in soft tissue and bone pathology. One study of sarcoma diagnosis based on a review of histopathology detected a 24% rate of discordance in diagnosis between community pathologists and an expert sarcoma reference pathology group, of which 66% of the discordant cases were felt to be clinically relevant due to impact on treatment recommendations [4] . Of the cases diagnosed by referring institutions as sarcoma, 13% were diagnosed as diseases other than sarcoma at the reference center.…”
Section: Telemedicine For Sarcoma Diagnosismentioning
confidence: 99%